2000
DOI: 10.1128/mcb.20.17.6426-6434.2000
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase A and Mitogen-Activated Protein Kinase Pathways Antagonistically Regulate Fission Yeast fbp1 Transcription by Employing Different Modes of Action at Two Upstream Activation Sites

Abstract: A significant challenge to our understanding of eukaryotic transcriptional regulation is to determine how multiple signal transduction pathways converge on a single promoter to regulate transcription in divergent fashions. To study this, we have investigated the transcriptional regulation of the Schizosaccharomyces pombe fbp1 gene that is repressed by a cyclic AMP (cAMP)-dependent protein kinase A (PKA) pathway and is activated by a stress-activated mitogen-activated protein kinase (MAPK) pathway. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
103
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(109 citation statements)
references
References 65 publications
(60 reference statements)
6
103
0
Order By: Relevance
“…We previously reported that the inv1 + gene that encodes invertase is repressed in the presence of glucose (Tanaka et al, 1998). The transcription of inv1 + is regulated by Scr1p, which is required for glucose repression of inv1 + (Tanaka et al, 1998) and fbp1 + (Neely & Hoffman, 2000). Similarly, Scr1p may have repressed the transcription of gal10 + in 2 % glucose medium.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the inv1 + gene that encodes invertase is repressed in the presence of glucose (Tanaka et al, 1998). The transcription of inv1 + is regulated by Scr1p, which is required for glucose repression of inv1 + (Tanaka et al, 1998) and fbp1 + (Neely & Hoffman, 2000). Similarly, Scr1p may have repressed the transcription of gal10 + in 2 % glucose medium.…”
Section: Discussionmentioning
confidence: 99%
“…The numbers indicate the TSS position of each transcript (in base pairs) from the A residue of the first ATG in the fbp1 ϩ gene. UAS1 and UAS2 represent the binding sites of Atf1 and Rst2, respectively (24,33). (B) Northern analysis to detect fbp1 ϩ transcripts.…”
Section: Methodsmentioning
confidence: 99%
“…Php5, a component of the S. pombe CCAATbinding factor (CBF; also known as NF-Y) that possesses a histone hold domain, forms a complex with Php2/Php3 and contributes to cyc1 ϩ transcription (31,32). In addition, two cis-acting elements required for fbp1 ϩ transcription have been identified (33). Upstream activation sequence 1 (UAS1) contains a cyclic AMP response element (CRE) and is the binding site for Atf1 and its binding partner, Pcr1 (34), while UAS2 resembles the S. cerevisiae stress response element (STRE) and serves as the binding site for Rst2 (24) (Fig.…”
mentioning
confidence: 99%
“…S. pombe is no exception and fundamental processes, such as the cell cycle (Wilkinson & Millar 2000) and gene expression in response to environmental signals (Neely & Ho¡man 2000;Bonnet et al 2000), are under the integrated, and mostly antagonistic, control of both pathways. The ultradian clock exerts control over the cell cycle (Kippert 2001b) and energy metabolism (Kippert & Read 2001), and it seems likely that much of this control involves the cAMP/PKA and sty1 + MAP kinase pathways.…”
Section: Cellular Signalling and Clock Functionmentioning
confidence: 99%